Chasing freedom the Philippines' long journey to democratic ambivalence - Webb, Adele (Ateneo de Manila University Press, 2021)
"How did Rodrigo Duterte earn the support of large segments of the Philippine middle class, despite imposing arbitrary rule and offering little tolerance for dissent? Has the Filipino middle class, heroes of the 1986 People Power Revolution, given up on democracy?